2020
DOI: 10.1177/0391398820948870
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound score as an indicator of dynamic lung compliance during veno-venous extra-corporeal membrane oxygenation

Abstract: Decisions on weaning from veno-venous extra-corporeal membrane oxygenation (VV-ECMO) requires the ability to maintain adequate gas exchange and work of breathing with reductions in ECMO pump flow and fresh gas flow. Testing of the readiness to wean the patient from ECMO however may vary dependent upon local protocols and clinical judgment. This study sought to validate the use of the LUS-score during VV-ECMO against the changes in chest x-ray infiltrates, dynamic lung compliance (CLdyn) and VV-ECMO settings (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…However, these data are lacking and we only know that, in adult ARDS patients, lung compliance correlates with the amount of aerated lung tissue being proportional to the residual ventilable lung volume: the smaller the open lung, the lower the compliance [ 13 ]. Furthermore, a recent case series reported a negative correlation between LUS and dynamic compliance in 10 adults undergoing veno-venous extra-corporeal membrane oxygenation (ECMO) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these data are lacking and we only know that, in adult ARDS patients, lung compliance correlates with the amount of aerated lung tissue being proportional to the residual ventilable lung volume: the smaller the open lung, the lower the compliance [ 13 ]. Furthermore, a recent case series reported a negative correlation between LUS and dynamic compliance in 10 adults undergoing veno-venous extra-corporeal membrane oxygenation (ECMO) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three RCTs ( Yang et al, 2019 ; Yang, 2019 ; Liu et al, 2020 ) evaluated the lung injury severity based simply on oxygenation criteria (PaO2/FiO2) (by calculating with PaO2/FiO2 when the fresh gas flow was off at the time of the arterial blood gas sampling, a higher score means lower percentage oxygenation and more severe lung injury) ( Ntoumenopoulos et al, 2021 ). Those three trials focused on adults and compared herbal remedies that included F. japonica plus usual care with usual care: Shufeng Jiedu capsule could significantly reduce the score in acute RTIs (MD -3.49, 95% CI [-3.96 to -3.03]) ( Liu et al, 2020 ) and in acute exacerbation of chronic obstructive pulmonary disease (AECOPD) (MD -3.49, 95% CI [-3.96 to -3.03]) ( Yang et al, 2019 ); and Xuanfei Quyu Tongluo liquid was less likely to reduce the score in AECOPD than usual care (MD -0.60, 95% CI [-0.98 to -0.22]) (Yang Q 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Systematic prospective multi-institutional studies indicated that EVLW is directly correlated to PaO 2 /FiO 2 and OI ( 22 24 ). Moreover, a strong negative association between LUS score and Cdyn at 48 h, Day 5 and Day 10 of commencement of VV-ECMO was observed in adult patients with ARDS ( 25 ). Consistently, our study revealed that LUS score mildly increased within 24 h, then gradually decreased after 72 h ECMO support in survivors.…”
Section: Discussionmentioning
confidence: 96%